An Active Pattern Infrastructure for Domain-Specific Languages - Levendovszky, Tihamer; Karsai, Gabor (Electronic Communications of the EASST, 2010)
Tool support for design patterns is a critically important area of computer-aided software engineering. With the proliferation of Domain-Specific Modeling Languages (DSMLs), the adaptation of the notion of design patterns appears to be a promising direction of research. This paper introduces a new approach to DSML patterns, namely, the Active Model Pattern infrastructure. In this framework, not only the traditional insertion of predefined partial models is supported, but interactive, localized design-time manipulation of models. Optionally, the infrastructure can be adapted to handling transactional tracing information as well as transactional undo and redo operations. Possible realizations of the framework are also discussed and compared